Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
ZenodoArchiveID: 3744581 previousshortDOI: 10/ghgng7 previousDOI: 10.5281/zenodo.3744581 EdTechHub.Source: 2405685:2WY8H4WW EdTechHub.Source: <this> shortDOI: 10/ghgng7 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3744581 10.5281/zenodo.3744581 10.53832/edtechhub.0021 10/ghgng7 2129771:QEIBUIQH 2339240:3NRFPYGI 2339240:TK94XQR9 2339240:XJRI6FW3 2339240:Y635S3D4 2339240:Z7XXM8CG 2339240:ZZ8ISXSK 2405685:2WY8H4WW 2405685:6FFSC2Z8 2405685:DI4SGTPH 2405685:FLHI5BHC 2405685:FVE6PDBB 2405685:GG9HHSDL 2405685:PXAIRTEK 2405685:RLBPSG29
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10610797 ZenodoArchiveConcept: 10610796 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1007 2339240:SZE9FBW4 2405685:IIAMD77T
Keywords: _r:AddedByMyEducationEvidence

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH